Numerical Solution of a Uniform Beam Problem Using g-spline-Based Differential Quadrature Method - Mohammed, Osama H; Fadhel, Fadhel S; Saeed, Mustafa A (Al-Nahrain Journal of Science, 2013)
The differential quadrature method with Chebyshev Gauss Lobatto sampling points is introduced for the modeling of vibration of a uniform beam. The g-spline interpolation function is utilized to obtain the explicit formula of the weighting coefficients for approximation of derivatives. Numerical example is presented to demonstrate the validity and accuracy of the proposed method.